Representation of Christianity in 'Farcry 5' - Jusuf Ariz Wahyuono (Program Studi Ilmu Komunikasi Universitas Bakrie, 2020)
Farcry 5 is a popular game in Indonesia and a 2018 first-person shooter game developed and published by Ubisoft. This game uses many symbols in the Christianity religion. Reading this game is crucial knowing that Indonesia has one of the largest concentrations of Christianity in the Muslim world. Using semiotic text-based analysis, we observed how this game represents religion using the structure of religious teachings in the Christianity tradition through symbols in the depiction of characters and narrative plots. The study focuses on Joseph Seed’s character and its environment. Joseph Seed is described as a Father, has a Bible, is part of a militia group, and a figure who has the qualities of a prophet. In the Storyline, Joseph Seed was shown as the one who receives the revelation, has Prophecy, and makes sacrifices. As Indonesia is a multicultural country, understanding religious representation in media is important. There are also fewer studies and concerns in popular media, especially in video games, despite its widely accessible content across Indonesia. This game received commercial success and became the fastest-selling title in the franchise, grossing over 310 million in its first week of sales.